Interactive multimedia animation in semiconductor devices. - Sihar, Suzaini; Ab Aziz, Sidek; Sulaiman, Zainal Abidin; Yahya, Noorhana (2007)
The growing corncern of teachers to improve their theoretical classes together with the revolution and methods brought about by the new information technologies combine offering students a new attractive, efficient and agreeable form of learning. The case of Fundamental of Semiconductor Devices' is particularly special, since the main purpose of this project is to overcome the student's misconception on several topics of semiconductor devices and to develop an ebook of Semiconductor Devices. Graphical animated presentations were designed to provide a solution to overcome misconception. A pre-test and post-test were carried out, to monitor the student's performance before and after using the software. The significant different between pre-test 1 and post-test 1 (pilot test) with sigma value for post-test 1 with confidence interval of 0.000 «0.05). The results for posttest 3 (experimental treatment) gives similar sigma value as post-test 1. Meanwhile, the students' perception towards the courseware prototype is positive and inline with the applicable presentation of interface in mUltimedia with the meari score value excess of 4.16 (sd=0.76) for each items given. The results indicate that the software offers students a real life understanding of applicable concept.